Rancang Bangun Alat Pembersih Panel Surya Dengan Time Scheduling: Rancang Bangun Alat Pembersih Panel Surya Dengan Time Scheduling - Prahmana Karyatanti , Iradiratu Diah; Dewantara, Belly Yan; Mughni, Faisal Akbar (J-Eltrik, 2024)
Utilization of solar energy using solar panels in Indonesia is currently only 0.05% of the existing potential. Where, Indonesia is a country located on the equator, so Indonesia has the potential to get stable solar energy. However, there are several factors that can reduce the optimality of solar panels. The factors that affect the optimal performance of a solar panel are the influence of temperature, the effect of shadows, and the material of the solar cell itself. If the cover glass, which is the outermost layer of the solar panel, is covered by dust or other barrier materials, this will block the entry of the intensity of sunlight and greatly affect the process of the photoelectric effect on the cell panel so that the electrical energy produced is not optimal, this event is called shading affect. In this study, a solar panel cleaning tool was designed based on time scheduling. This tool is used to reduce dust and other obstructions on the surface of solar panels. If there is no dust and dirt around the solar panel, this cleaning tool will clean the solar panel automatically.